ANALISIS PENGARUH KUALITAS KOHESIVITAS GURU TERHADAP KOMPETENSI GURU DENGAN KUALITAS PEMBELAJARAN ORGANISASI SEBAGAI VARIABEL INTERVENING DI SMP NEGERI 2 PURWODADI - Hardiyanti, Neisha; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of the study is to determine, describe and analyze the more influence the quality of teachers to the cohesiveness of the competence of teachers to the quality of the learning organization as an intervening variable. The method of collecting data in this study using questionnaires with respondents 50 teachers, where the respondent is a total population of taechers SMPN 2 Purwodadi. Data analysis method used is multiple linear regression analysis. Mechanical testing of the data in this study using path analysis and Sobel test to test the effect of mediation.The results showed that the quality of cohesiveness teachers have positive and significant impact on the quality of a learning organization. Cohesiveness quality of teachers and the quality of organizational learning has a positive and significant impact on teacher competence. In addition, the quality of organizational learning may mediate the relationship between the quality of teachers to the cohesiveness of teacher competence.